La movilización electoral de la nueva derecha chilena para el rechazo a la nueva Constitución chilena - Quiroga Aguilar, Lautaro Elías; Lara Órdenes, Eliseo Esteban (Pontificia Universidad Católica del Perú, 2025)
Despite having different organizational moments, the comparative analysis of the Chilean center-right parties reveals that the oldest groups have a clear tendency towards elitization, decentralization and a more marked business profile. The present research seeks to characterize the agenda-setting strategy and media concentration by the center-right in Chile that mobilized the rejection of the proposed new constitution. This research uses the process tracing analysis methodology to describe agents and processes of the cabinet of the second government of Sebastián Piñera, considered an example of the phenomenon of businessmen presidents in Latin America. We conclude that large economic groups financed the rejection campaign of strategic agents of the Chilean center-right, which allowed concentrating the media and activating the reticular expansion that center-right think tanks have configured in their relationship with economic groups. The identification of networks, agents and processes in the articulation of power offers perspectives on the reproduction of power and its relationship with inequality.

A pesar de poseer distintos momentos organizacionales, el análisis comparativo de los partidos de la centroderecha chilena revela que los grupos más antiguos poseen una tendencia clara a la elitización, la descentralización y un perfil empresarial más marcado. La presente investigación busca caracterizar la estrategia de creación de agenda y concentración de medios de comunicación por parte de la derecha en Chile que movilizó el rechazo a la propuesta de una nueva Constitución. La metodología utilizada es process tracing analysis para describir agentes y procesos del gabinete del segundo gobierno de Sebastián Piñera, considerado un ejemplo del fenómeno de presidentes empresarios en América Latina. Concluimos que los grandes grupos económicos financiaron la campaña del rechazo a agentes estratégicos de la derecha chilena, lo que permitió concentrar los medios de comunicación y activar la expansión reticular que los think tanks de centroderecha han configurado en su relación con los grupos económicos. La identificación de redes, agentes y procesos en la articulación del poder ofrece perspectivas la reproducción del poder y su relación con la desigualdad.
The Electoral Mobilization of the New Chilean Right for the Rejection of the New Chilean Constitution
Keywords: Think tanks; Corporate elite; State capture; Economic groups; Chilean right; Think tanks; Élite corporativa; Captura del Estado; Grupos económicos; Derecha chilena; https://purl.org/pe-repo/ocde/ford#5.04.00